Inteligencia Artificial y Buen Gobierno Corporativo - Porto, José Miguel (2024)
This article exposes artificial intelligence as a tool to strengthen the good corporate governance of Peruvian companies. In a corporate market where the ownership and management of companies are in the hands of controlling shareholders, this structure generates other structural problems of sustainability in the long term, since the company’s control bodies are captured by the controlling shareholders and decisions tend to benefit the controlling shareholders immediately to the detriment of the long-term sustainability of the business. How can good corporate governance incentives be generated so decisions are aimed at promoting the long-term sustainability of the business? How can corporate bodies make decisions that benefit the environment and society in general (ESG), rather than the controlling shareholders they serve? We believe that the incorporation of artificial intelligence can play a leading role in corporate governance if its participation in the board of directors or management of companies with algorithms that favor ESG is allowed.